Preparative and capillary isoelectric focusing for detection and identification of Aspergillus conidia in complex sample matrices - Horká, Marie; Šalplachta, Jiří; Růžička, Filip; Šlais, Karel (Journal of separation science, 2018)
This study describes a new method for fast identification of highly hydrophobic conidia of Aspergillus species from both simple and complex matrices. The method is based on recently developed preparative isoelectric focusing in a cellulose-based separation medium which had to be modified with respect to the highly hydrophobic surface of the conidia. Although Aspergillus conidia are colored, their zones in the cellulose bed were indicated by colored isoelectric point markers. The isoelectric point values of Aspergillus conidia were determined by capillary isoelectric focusing. Preparative isoelectric focusing was successfully used for preconcentration of individual conidia of cultivated strains of Aspergillus niger, Aspergillus fumigatus, Aspergillus flavus, and Aspergillus parasiticus, and also for separation of the conidia in a mixture. Subsequently, red pepper powder and peanuts spiked with Aspergillus niger and Aspergillus flavus conidia, respectively, were used as complex matrices. The detection limit for identification of the conidia in these complex matrices is 104 conidia mL-1 . The presence of conidia in the focused zones was confirmed by their subsequent analysis by capillary isoelectric focusing. Their viability was confirmed by a cultivation of the conidia extracted from the collected fractions after preparative isoelectric focusing.
Keywords: Spores, Fungal; Capsicum; Isoelectric Focusing; prášky, zásypy, pudry; Arachis; isoelektrická fokusace; spory hub; Aspergillus; Powders